A Massive Right Atrial Mass in Chronic Myelogenous Leukaemia: A Case Report and Literature Review - Juthipong Benjanuwattra; Mahmoud Abdelnabi; Rubayat Rahman; Leigh Ann Jenkins (European Journal of Case Reports in Internal Medicine, 2022)
Right atrial masses are rare and diagnosis can be difficult unless histopathological specimens are obtained. In addition, the clinical course is not well documented, thereby making diagnosis and management challenging. The mass can be associated with haemodynamic instability with the potential to cause obstructive shock and embolism. We present the case of a young woman with untreated chronic myelogenous leukaemia with a massive haemodynamically significant right atrial mass. The usefulness of multimodality imaging and a multidisciplinary approach for diagnosing and treating this condition is highlighted.